Utilizing Wordtune as A Digital Writing Assistant to Enhance Students’ Writing Skill: English - Dwi Andina; Pirman Ginting (Journal of English Development, 2024)
Writing is a critical language skill that students must acquire; nevertheless, the teaching and learning process for writing in the classroom does not go smoothly. As a result, the purpose of this study is to examine Wordtune's potential as a digital writing aid to enhance the written proficiency of English as a foreign language (EFL) students. To accomplish this goal, a pre-experimental research design was used with quantitative research tools. The pre- and post-tests were employed as tools for gathering data. Twenty students in grade ten at SMK-BM PAB 3 Medan Estate, majoring in MPLB and AKL, served as the sample for this study. Tests were given both before and after the intervention to gather data. The significant difference between the pre-and post-tests was analyzed statistically using SPSS with the T-test. The result indicates that the probability value for pre-test and post-test data is 0.000, the Tcount value is 26.536, and the Ttable value is 2.093. Because the value of Tcount > Ttable is 26.536 > 2.093 and the probability value (Sig.) 0.000 < 0.05. As a result, the use of Wordtune considerably enhanced students' writing skills. As this study demonstrated, Wordtune can be integrated into the learning process to help students write more successfully.